(untitled) (Damascus University Journal for engineering sciences, 2021)
There are many ways of operations to transform flat surfaces composed of multiple elements that have different geometric shapes to spatial surfaces. One of the most important economic conditions, and sometimes aesthetic ones, in the formation of these surfaces is for number of models we used to be at its minimum while having the same measurements. In this subject of research we study the conversion ringed flat surfaces formed of two geometric models, with varying measurements, to spatial paved surfaces rotational models of the same, shapes of static and repetitive dimensions, which gives a more aesthetic form and the best economic sense. These surfaces are called surfaces rotational or cyclic surfaces rotary tower. We started the study using two models (a triangle and a rectangle), and then we moved to the other two models (a triangle and a trapezoidal), where we found that changing some of the values of variables opens the way for a different rotational surfaces. This study can be used to develop more models to choose (rectangle, triangle and trapezoid)